Nutritional analysis and biochemical tests of people living with HIV in Belém – Pará – Brazil (Research, Society and Development, 2023)
Introduction: The HIV virus and the drugs used to treat the infection generate unfavorable effects on the human body, whether at a cellular or macroscopic level, such as the destruction of CD4 T lymphocytes and changes in adipose tissue. These dysfunctions have a direct impact on the nutritional status, which must remain adequate for a positive prognosis. Objective: to evaluate biochemical, nutritional and lifestyle parameters of people living with HIV. Method: cross-sectional, descriptive and analytical study with a sample of 50 patients of both sexes, aged between 18 and 60 years, who use antiretroviral therapy, treated at the outpatient clinic of the João de Barros Barreto University Hospital (HUJBB/UFPA). Results: Of the research participants (n=50, 100%), 40% (n=20) had high blood glucose, 30% (n=15) borderline triglycerides and 60% (n=30) low HDL. Regarding life habits, 56% (n=28) declared themselves to be sedentary, 20.4% (n=10) smokers and 36% (n=18) drink alcohol. In the nutritional context, the survey showed that most are overweight/obese according to BMI (n=25, 50%) and eutrophic according to ACB% (n=30, 60%), with 52% (n=26 ) are at cardiovascular and metabolic risk.  Conclusion: There was a considerable frequency of sedentary people with changes that reflect on the nutritional status, requiring a more careful, individualized and multidisciplinary analysis aimed at improving the quality of life and controlling the infection.